Relationship Between Tranparancies Of Funding Objectives And Work Ethics Of The Local Government Apparatus In Minahasa - Frida Magda Sumual (IAIN Manado, 2018)
This research aims to discover the relationship between tranparancies of funding objectives and work ethics of the local government apparatus in Minahasa. The public sector development in Indonesia should be followed by research on work ethics concept in order to prepare good apparatus as public duties. This research analyses data quantitatively using non parametric statistic test X2. To simplify the analysis cross tabulation is created so data on the table can be analised to test the hypotheses. This research collects qualitative and quantitave data. Field obsevation is used as data collection instrument. The research finding shows that there is a significant relationship between tranparancies of funding objectives and work ethics of the local government apparatus 0,56 %. The funding objectives tranparancies determine the size of funding objectives specificly and understood by whom responsible. Government apparatus will react positively and relatively strong to increase the funding objectives tranparancies. Superior leaders can increase job satisfACTION lower job strength and increase fuunding related to work ethics.Keywords: Transparancy Of Funding Objectives, Work Ethics.